Costumer Satisfaction On Wedding Organizer During The Covid-19 Pandemic (Adinata Wedding Organizer Case Study) - Sefina Isna Asaroh; Mar'atul Fahimah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the influence of people, process, and physical evidence on costumer satisfaction at adinata wedding organizers during the covid-19 pandemic. This type of research is associative research. with the form of research is a quantitative approach. the sampling technique used purposive sampling, the respondents of this study were contumers who used the services of a wedding organizer from March 12, 2020 to June 12, 2021 with a total sample of 40 respondents. Data collection techniques using the method of observation and questionnaires. The research instrument used in this study was a questionnaire (Questionnaire). The data analysis technique in this study uses multiple linear regression, partial T test and simultaneous F test, the data is processed using the SPSS 26 program. The results of this research show that there is no significant effect of people on costumer satisfaction, while process has a significant effect on customer satisfaction. and physical evidence has a significant influence on contumer icon satisfaction in choosing Adinata wedding organizer services during the covid-19 pandemic.